Non-inferiority study of the efficacy of two hyaluronic acid products in post-extraction sockets of impacted third molars - Hyunwoo Yang; Junghun Kim; Jihong Kim; Dongwook Kim; Hyung Jun Kim (SpringerOpen, 2020)
Abstract Background Hyaluronic acid (HA) is well known to exert an anti-inflammatory effect during oral wound healing and is commonly applied after tooth extraction. However, no double-blind randomized controlled study comparing two hyaluronate mouthwash products has been conducted so far. The aim of this study was to comparatively analyze the efficacy of Mucobarrier® and Aloclair® in terms of clinical symptoms. Results A total of 112 patients were randomly assigned to assess the degree of discomfort, pain reduction, redness, burning sensation, and swelling between two groups on the day of surgery and 7 days later in a double blind test, with a total 56 Aloclair patients and 56 Mucobarrier patients. There was no statistically significant difference in the overall discomfort, degree of pain reduction, redness, burning sensation, and swelling between the Mucobarrier and Aloclair groups. Conclusion The local application of hyaluronic acid mouth wash after wisdom tooth extraction is beneficial in reducing overall discomfort and pain reduction, and the clinical utility of Mucobarrier® is no different from Aloclair®. Trial registration Institutional Review Board of Yonsei University College of Dentistry, 2-2018-0036. Registered 10 September 2018-prospectively registered, https://eirb.yuhs.ac/